1976
DOI: 10.3109/10826087109045533
|View full text |Cite
|
Sign up to set email alerts
|

Addiction to Diazepam

Abstract: Literature is reviewed which raises the question of diazepam's addicting potential. To explore this issue, 50 subjects referred from medical, surgical, and psychiatric clinics were evaluated by interview regarding their use of diazepam. Replies to a standardized interview were combined with physicians' ratings of addiction under two conditions: without and then with the knowledge that the drug in question was diazepam. A computer-aided analysis of these data, including a correlation matrix, revealed surprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Maletzky and Klotter [56] reviewed 27 articles in which diazepam was claimed to be free of addicting properties, and concluded that none had used adequate methods. Systematic withdrawal were not carried out, and in some, no data regarding tolerance were collected.…”
Section: Clinical Dependencementioning
confidence: 99%
“…Maletzky and Klotter [56] reviewed 27 articles in which diazepam was claimed to be free of addicting properties, and concluded that none had used adequate methods. Systematic withdrawal were not carried out, and in some, no data regarding tolerance were collected.…”
Section: Clinical Dependencementioning
confidence: 99%
“…Maletzky (12) reported that even when not taking excessively high doses many patients •• ParafonForte had difficulty in decreasing or discontinuing their dose.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a growing number of reports on Diazepam abuse has been published (3,(5)(6)(7)9,(12)(13)(14)(15). Diazepam is known to produce both physiological and psychological dependence and addiction.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 This may be either alone or in combination with analgesics, 47 or to patients in whom migraine is associated with tension headache. 48 While tension headache and migraine are distinct clinical entities, 49 it is germane to examine the so called "tension" trigger in migraine. However, recent evidence suggests that benzodiazepine dependence occurs more frequently than has been recognized.…”
Section: Justification For Use: a Brief Reviewmentioning
confidence: 99%
“…However, recent evidence suggests that benzodiazepine dependence occurs more frequently than has been recognized. 48 While tension headache and migraine are distinct clinical entities, 49 it is germane to examine the so called "tension" trigger in migraine.…”
Section: Justification For Use: a Brief Reviewmentioning
confidence: 99%